Language Expression of the Courtesy Category (The Peerian Journal, 2022)
The article identifies the parameters that allow us to present a model of this speech genre in Russian and Uzbek. It is characterized by language learning in connection with the speaker's communicative intentions and in connection with the strategies that the speaker chooses to achieve his goals. At the same time, the language is considered as a means of communication, inextricably linked with the culture of the people who speak this language